Feasibility of recycling sewage sludge ash in ultra-high performance concrete: Volume deformation, microstructure and ecological evaluation. (7th February 2022) - Gu, Chunping; Ji, Yongjie; Yao, Jikai; Yang, Yang; Liu, Jintao; Ni, Tongyuan; Zhou, Hangjie; Tong, Yunyun; Zhang, Xuefeng
Graphical abstract: Highlights: Replacing 10% cement with sewage sludge ash (SSA) in UHPC is feasible. SSA enlarged the autogenous and drying shrinkage of UHPC. UHPCs with SSA expanded in water due to the high SO3 content in SSA. The addition of SSA reduced the environmental impact of UHPC. Abstract: Sewage sludge ash (SSA) is a kind of solid waste which has to be dealt with. Recycling SSA in ultra-high performance concrete (UHPC) as cement replacement is a possible solution. However, related attempts haven't been made yet. In this paper, the effects of SSA on the fluidity and strength of UHPC were studied. The volume deformation of UHPCs under different environmental conditions and the microstructure of UHPC with SSA were investigated. The environmental evaluation on UHPC containing SSA was performed, and the feasibility of recycling SSA in UHPC was discussed. The results showed that the addition of SSA gradually reduced the fluidity and flexural strength of UHPC. The 3d compressive strength of UHPC was also decreased with higher SSA content; however, the7d and 28d compressive strength of UHPC with 10% SSA was slightly increased. The autogenous shrinkage and drying shrinkage were enlarged by adding SSA. Nevertheless, UHPCs with SSA showed expansion when immersed in water. In addition, the presence of SSA reduced the hydration heat release and increased the pore volume of UHPC. Ettringite and CaSO4 were observed in UHPC with SSA due to the high content of SO3 in SSA. The environmental evaluation showed that the recycling use of SSA reduced the environmental impacts of UHPC. Conclusively, it is possible to recycle SSA in UHPC, but further studies are needed to control the volume deformation of UHPC caused by the presence of SSA.